Language Politeness Strategies Spoke by Boy William in the Breakout Interview with Ruel - Rifti Asri Meiliana; Rahmawati Sukmaningrum; Th. Cicik Shopia B. (Lingua Franca, 2023)
This study aims to (1) find out the types of politeness strategies spoken by Boy William in a breakout interview with Ruel, (2) find the most dominant politeness strategies, and (3) find the contribution of politeness strategies from a pragmatic perspective. This research is qualitative. The research data is in the form of a conversation between Boy William and Ruel in the talk show "Breakout Interview with Ruel" on the YouTube channel. The research data was taken from Boy William's speech when communicating with Ruel. The research data were analyzed using Miles and Huberman's descriptive qualitative model theory (2014). Research data was collected by watching talk show videos on YouTube, listening, recording, analyzing, and classifying the speaker's speech (Boy William) when communicating with the guest star (Ruel). The results of the study stated that 21 utterances had been analyzed as language politeness strategies spoken by Boy William in the Breakout Interview Talkshow with Ruel, namely; 12 (57.142%) positive politeness strategies, 4 (19.047%) Bald Off Record, 1 (4.761%) %) negative politeness and 4 (19.047%) Off Record. It can be concluded that Boy William tends to use positive politeness strategies more often in interviewing guests (Ruel).